Effect of the COVID-19 pandemic on the epidemiological trends and outcomes of gastrointestinal bleeding: a nationwide study. Issue 2 (4th March 2023) - Kwei-Nsoro, Robert; Ojemolon, Pius; Laswi, Hisham; Ebhohon, Ebehiwele; Ufeh, Annabel Ogar; Nieto, Alejandro; Mir, Wasey Ali; Shaka, Abdultawab; Shaka, Hafeez
Abstract: The COVID-19 pandemic altered healthcare delivery in the United States. This study examined the effect of the COVID-19 pandemic on the epidemiological trends and outcomes of gastrointestinal bleeding. We compared the admission rate, in-hospital mortality rate, and mean length of hospital stay between 2019 and 2020 to estimate the pandemic effect. The study highlighted disparities in outcomes of gastrointestinal bleeding hospitalizations stratified by sex and race. We noted a 9.5% reduction in the total number of hospitalizations in 2020. We also observed a 13% increase in overall mortality during the pandemic ( P  < 0.001). There was a 15.8% increase in mortality among men ( P =  0.007), compared to a 4.7% increase among women ( P =  0.059). There was a significant increase in mortality among Whites in 2020 compared to Black and Hispanic populations. On multivariable logistic regression, admission during the COVID-19 pandemic was associated with increased length of stay when adjusted for age, sex, and race. Despite the direct COVID-19–related morbidity and mortality, the so-called indirect effect of the pandemic cannot be overlooked. For the remainder of the pandemic and future health emergencies, it is critical to balance mitigation of the spread of the contagion with clear public health messages to not neglect other life-threatening emergencies.